Analisis Kapasitas Terminal Penumpang dan Lapangan Parkir Pelabuhan Bajoe Kabupaten Bone - Nasruddin, Rini Safitri; Djafar, Wihdat; Djalante, Abdul Haris; Misliah, Misliah; Chairunnisa, Sitti (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
Bajoe Port is a ferry port using Ro-Ro type ships that transport passengers, goods and vehicles from several districts/cities in South Sulawesi to Kolaka Regency, Southeast Sulawesi Province. The aim of this research is to predict the number of passengers and vehicles that will visit Bajoe Harbor until 2037 and determine the need for passenger terminals and parking lots that are currently available until 2037. The method used is regression to predict the flow of ships, passengers and vehicles as well as a formula for calculating the needs of passenger terminals and parking lots in determining capacity. The results of the research are predictions of the number of passengers and vehicles that will visit Bajoe Harbor until 2037 at 498,168 people and 76,038 units. The passenger terminal capacity until 2037 is 1,497 m² so that the current available passenger terminal capacity of 1,459 m2 is no longer sufficient until 2037 and additional passenger terminal capacity is needed. The parking capacity of vehicles that will cross and delivery/pick up vehicles until 2037 is 1,771 m² and 839 m2 so that the parking capacity of vehicles that will cross and delivery/pick up vehicles currently available is 8,980 m2 and 2,984 m2, which is still sufficient until 2037 and is not it is necessary to increase the parking capacity of vehicles that will be crossing and delivery/pick up vehicles.